Survey on the use of drugs to treat gastric and duodenal ulcers at Thuan Thao General Clinic - Nguyen, Thị Trà My; Le, Văn Út; Nguyen, Thị Ánh Tuyết (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Gastric and duodenal ulcers are chronic, cyclical diseases that recur and cause many dangerous symptoms. The disease is not only common in developing countries but also in developed countries. Currently, the use of drugs in a reasonable - safe - effective manner is always a top concern of the medical profession. Therefore, "Survey on the use of drugs to treat gastric and duodenal ulcers at Thuan Thao General Clinic" was conducted. Results: Most of the patients are female, with an average age of 39.36 ± 12.40. Gastritis is a common disease group (80.05%) with the main symptom being pain in the epigastric region. The most commonly used main treatment group is PPI (86.11%). The commonly used treatment regimen is clarithromycin + amoxicillin + PPI (95.12%), the treatment time is mostly during the promotional period (83.59%). Most of the interactions were moderate and mild, requiring PPI and iron regimens. Regarding treatment efficacy, 57.07% of patients were supportive, 33.84% of patients were cured, and a small number of patients had no change in their condition, accounting for 9.09%.